E-Leadership: Concept and Influence of Digital Leadership - Sukmawati, Murni; Giatman, M.; Maksum, Hasan (Jurnal Teknologi Informasi dan Pendidikan, 2024)
Information and communication technology has brought significant changes in the world of education, including at Universitas Negeri Padang. The concept of E-Leadership, or leadership in a digital context, is a major highlight in dealing with this transformation. This article explains the concept of E-Leadership and its impact on the leadership context at Universitas Negeri Padang. The concept of E-Leadership involves applying technology to lead, manage and communicate effectively. The influence of digital leadership in universities includes increased accessibility and flexibility, learning transformation, effective collaboration, university management innovation, and new leadership challenges and skills. This article discusses how leaders at Universitas Negeri Padang can adopt E-Leadership to optimize the use of technology to achieve more responsive and innovative educational goals.